2018
DOI: 10.1055/s-0038-1676087
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of ADHD Information between Parents and Teachers Using an EHR-Linked Application

Abstract: Background Appropriate management of attention-deficit/hyperactivity disorder (ADHD) involves parents, clinicians, and teachers. Fragmentation of interventions between different settings can lead to suboptimal care and outcomes. Electronic systems can bridge gaps across settings. Our institution developed an email-based software to collect ADHD information from parents and teachers, which delivered data directly to the clinician within the electronic health record (EHR). Objective We sought to adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…53 Investigators at Children's Hospital of Philadelphia developed the ADHD Care Assistant, a system that sends electronic ADHD rating scales to parents and teachers, presents results seamlessly in the EHR and allows parents to elect automated sharing of ADHD information between themselves and teachers, thereby facilitating communication. 55 Michel et al 56 found that most parents are amenable to sharing ADHD rating scale information collected in the system with teachers, but parents viewed only 16% of teachersubmitted ADHD surveys, and teachers viewed 30% of parent surveys. The investigators concluded that in future efforts, researchers should target the development of strategies to encourage viewing of shared information.…”
Section: Ehr-based Systemsmentioning
confidence: 99%
“…53 Investigators at Children's Hospital of Philadelphia developed the ADHD Care Assistant, a system that sends electronic ADHD rating scales to parents and teachers, presents results seamlessly in the EHR and allows parents to elect automated sharing of ADHD information between themselves and teachers, thereby facilitating communication. 55 Michel et al 56 found that most parents are amenable to sharing ADHD rating scale information collected in the system with teachers, but parents viewed only 16% of teachersubmitted ADHD surveys, and teachers viewed 30% of parent surveys. The investigators concluded that in future efforts, researchers should target the development of strategies to encourage viewing of shared information.…”
Section: Ehr-based Systemsmentioning
confidence: 99%
“…This allows family members to become team members in the management of a child’s ADHD. To improve communication and collaboration between professionals in health care and education and facilitate the use of evidence-based assessment and intervention across home and school contexts, Power and colleagues developed and refined the ADHD Care Assistant (Michel et al, 2018; Power et al, 2016). Other electronic systems exist, but they are not directly linked to the health care electronic system (Epstein et al, 2013).…”
Section: Effective Leadership and Teamworkmentioning
confidence: 99%
“…The ADHD Care Assistant has four distinct features: (a) an electronic survey designed to collect data from parents and teachers, (b) a module visible to providers and integrated into the electronic health record (EHR) system, (c) a web service design to facilitate communication between the shared data and the EHR, and (d) an e-mail-based platform for sharing data between parents and teachers (Michel et al, 2018; Power et al, 2016). One of the particular benefits of the ADHD Care Assistant is the opportunity it affords parents to select preferred treatments for the child, including medication and/or behavior therapy, and to share data among members of the health care team and with the child’s teachers.…”
Section: Effective Leadership and Teamworkmentioning
confidence: 99%
See 2 more Smart Citations